2014
DOI: 10.1039/c4mb00386a
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the potential extracellular electron transfer pathways from a c-type cytochrome network

Abstract: Extracellular electron transfer (EET) is the key feature of some bacteria, such as Geobacter sulfurreducens and Shewanella oneidensis. Via EET processes, these bacteria can grow on electrode surfaces and make current output of microbial fuel cells. c-Type cytochromes can be used as carriers to transfer electrons, which play an important role in EET processes. Typically, from the inner (cytoplasmic) membrane through the periplasm to the outer membrane, they could form EET pathways. Recent studies suggest that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…The four proteins were predicted to be located in periplasmic space by using online software 2 , which is consistent with the SorAB location in several other bacteria such as Starkeya novella and Aeropyrum pernix (Meyer et al, 2004;Denger et al, 2008). SorA often coexists with SorB for sulfite respiration (Myers and Kelly, 2005) and is predicted to have electronic interactions with trimethylamine N-oxide reductase (TorA) and nitrate ammonification protein (NapA) in S. oneidensis MR-1 (Ding et al, 2014). Our previous results showed that deletion of gene SHD2782 in S. decolorationis S12 resulted in 30% decrease in current generation (Kong et al, 2017).…”
Section: Different Transcriptomic Profiles Between Electrode and Amarsupporting
confidence: 61%
See 1 more Smart Citation
“…The four proteins were predicted to be located in periplasmic space by using online software 2 , which is consistent with the SorAB location in several other bacteria such as Starkeya novella and Aeropyrum pernix (Meyer et al, 2004;Denger et al, 2008). SorA often coexists with SorB for sulfite respiration (Myers and Kelly, 2005) and is predicted to have electronic interactions with trimethylamine N-oxide reductase (TorA) and nitrate ammonification protein (NapA) in S. oneidensis MR-1 (Ding et al, 2014). Our previous results showed that deletion of gene SHD2782 in S. decolorationis S12 resulted in 30% decrease in current generation (Kong et al, 2017).…”
Section: Different Transcriptomic Profiles Between Electrode and Amarsupporting
confidence: 61%
“…In S. decolorationis S12 periplasm, SorA co-exists with many other redox proteins, including those involved in EET. It is possible that SorA diverts electrons from the efficient EET pathways (e.g., cymA-MtrABC) to other electron pools (e.g., TorA and NapA) in the periplasm (Ding et al, 2014) and thus suppresses the current generation of strain S12.…”
Section: Roles Of Sora In Current Generationmentioning
confidence: 99%
“…Shewanella oneidensis MR‐1 is one of the most well‐known electricigens and can respire anaerobically by utilizing a wide variety of extracellular electron acceptors (termed extracellular electron transfer, EET) . Currently, the following four EET pathways have been proposed to fulfill EET processes: (a) the MtrCAB pathway (CymA → MtrA → MtrB → MtrC/OmcA), (b) the MtrDEF pathway (CymA → MtrD → MtrE → MtrF), (c) the DMSO pathway (CymA → DmsE → DmsF → DmsA/DmsB), and (d) the SO_4360‐57 pathway (CymA → SO_4360 → SO_4359 → SO_4358/SO_4357) . Briefly, the inner membrane c ‐type cytochrome CymA can gather electrons generated in the cytoplasm; then, with the periplasmic c ‐type cytochromes MtrA/MtrD/DmsE/SO_4360 and outer membrane proteins MtrB/MtrE/DmsF/SO_4359, these electrons can be transferred from CymA to the extracellular components MtrC‐OmcA/MtrF/DmsAB/SO_4358‐57, respectively, which can further transfer the electrons to extracellular electron acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…The electron transfer network was then modeled as an undirected graph, in which nodes represent the proteins and the links represent protein interactions. It is clear that network structure strongly correlates with its function, for example, several classical EET pathways have been identified by modular analysis of a c -type cytochrome network ( Ding et al, 2014 ). As k-shell analysis has been widely used to explain both the formation and current structure of networks ( Kitsak et al, 2010 ; Pei et al, 2014 ), we thus engaged this method to study the formation and extension of Shewanella electron transfer network and its functional parts, as well as their potential implications for EET processes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed the high efficiency of the prediction of biological pathways from biological networks ( Planas-Iglesias et al, 2012 ; Huang et al, 2013 ; Mukhopadhyay and Maulik, 2014 ). Following initial work on a small-scale c -type cytochrome network ( Zhang et al, 2008 ), a recent study constructed a network for all of 41 c -type cytochromes in S. oneidensis MR-1 and the classical EET pathways (e.g., MtrCAB, MtrDEF) can be identified from the c -type cytochrome network ( Ding et al, 2014 ). Furthermore, from the view of steric properties of individual proteins, Volkov and van Nuland (2012) performed extensive conformational sampling, mapped out functional epitopes in c -type cytochrome complexes (involving cytochrome c and other redox-active proteins such as peroxidase and cytochrome b 5 ) and then assessed the electron transfer properties of such interactions.…”
Section: Introductionmentioning
confidence: 99%